1990
DOI: 10.1038/jcbfm.1990.120
|View full text |Cite
|
Sign up to set email alerts
|

Focal Cerebral Ischemia in the Cat: Pretreatment with a Competitive NMDA Receptor Antagonist, D-CPP-ene

Abstract: Summary:The effects of the competitive N methyl-o-aspartate (NMD A) receptor antagonist 0-(E)-4-(3-phosphonoprop-2-enyl)piperazine-2-carboxylic acid (o-CPP-ene; SDZ EAA 494) upon ischemic brain damage have been examined in anesthetized cats. Focal cerebral ischemia was produced by permanent occlusion of the middle cerebral artery (MCA) and the animals were killed 6 h later. The amount of early ischemic brain dam age was assessed in coronal sections at 16 predetermined stereotaxic planes. Pretreatment with o-CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…12 Furthermore, reduction in caudate injury was not significant in earlier studies with MK-801, whereas striatal protection was observed with dextromethorphan. 39 We observed 49% and 64% reductions in caudate injury at the 5-and 50-mg/kg doses, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…12 Furthermore, reduction in caudate injury was not significant in earlier studies with MK-801, whereas striatal protection was observed with dextromethorphan. 39 We observed 49% and 64% reductions in caudate injury at the 5-and 50-mg/kg doses, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…- 12 However, efficacy of competitive NMDA antagonists administered at reperfusion after transient focal ischemia is unclear. The goal of the present study was to test the hypothesis that a competitive NMDA receptor antagonist decreases the volume of injury associated with 1 hour of transient focal ischemia when the drug is administered at two different doses 15 minutes before reperfusion.…”
mentioning
confidence: 99%
“…This is because competitive and noncompetitive 7V-methyl-D-aspartate (NMDA) antagonists have been shown to reduce infarct size to about 50% of control even though MCA occlusion is maintained. 6 " 10 Comparable effects have been obtained with some calcium antagonists. 11 -12 In all these cases, pharmacological treatment reduced damage to neocortical tissue without affecting the lesion to the focal areas encompassing the dorsolateral part of the caudoputamen and the adjacent neocortical areas.…”
mentioning
confidence: 94%
“…The physiological and pathological effects of glutamate in the CNS are mediated through its interaction with specific cell membrane receptors, of which the N-methyl-D-aspartate (NMDA), kainate, and AMPA subtypes are the best characterized [Monoghan et al, 1989]. The use of specific antagonists [Park et al, 1988;Monoghan et al, 1989;Bullock et al, 1990;Flood et al, 1990;Bashir et al, 1991;Tacconi et al, 1993;Hoffman et al, 1994] of the NMDA receptor support the role of receptor activation in LTP and hypoxic/ischemic cerebral injury. The NMDA-type glutamate receptor is a predominant mediator of excitotoxicity in the immature as compared to the adult brain due to overexpression of the receptor in the developing immature brain [Johnston, 1995].…”
Section: Introductionmentioning
confidence: 99%